2022
DOI: 10.2478/pomr-2022-0034
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Model to Manage Ship Fuel Consumption and Navigation Time

Abstract: Owners of vessels are interested in the lowest possible operating costs. These costs are mainly related to fuel consumption during navigation. To manage it rationally, the main decision-making problem is selecting the proper parameters of the ship’s propulsion system during navigation. In practice, operators of ships equipped with controllable pitch propellers controlled in manual mode make a selection of the commanded outputs based on their own knowledge, intuition, and all accessible information regarding se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Seaports or shipping are also part of the cause. A large number of studies have been carried out on the green and clean technological solutions for seaports and shipping such as toxic emission management [78][79][80][81][82][83][84], and utilization and application of clean energy relating to toxic emission and clean energy management become extremely important [85][86][87][88][89], ballast water treatment in seaport [90][91][92], treatment and management for oily water and polluted water sources by heavy metal caused by maritime activities [93][94][95][96][97][98][99][100][101].…”
Section: Seaportmentioning
confidence: 99%
“…Seaports or shipping are also part of the cause. A large number of studies have been carried out on the green and clean technological solutions for seaports and shipping such as toxic emission management [78][79][80][81][82][83][84], and utilization and application of clean energy relating to toxic emission and clean energy management become extremely important [85][86][87][88][89], ballast water treatment in seaport [90][91][92], treatment and management for oily water and polluted water sources by heavy metal caused by maritime activities [93][94][95][96][97][98][99][100][101].…”
Section: Seaportmentioning
confidence: 99%
“…(3) To obtain the hierarchical components 𝑋𝑋 𝑘𝑘,𝑒𝑒 of each layer in the hier process, the operator 𝑄𝑄 𝑗𝑗 𝑘𝑘 is used repeatedly. At the same time, define the o 1} and integer e = ∑ γ j 2 n−j n j=1 (4) Based on vector [𝛾𝛾 1 , 𝛾𝛾 2 ,••• , 𝛾𝛾 𝑛𝑛 ], the hierarchical component of the e-th can be calculated by 𝑋𝑋 𝑘𝑘 (5) For each 𝑋𝑋 𝑘𝑘,𝑒𝑒 , the coarse-gain sequence can be calculated by…”
Section: Multiscale Decompositionmentioning
confidence: 99%
“…These have become the main source of pollutants in the sea and coastal areas of ports, causing serious damage to the ecological environment and affecting people's health [4]. The fuel injection system of a marine diesel engine has an important influence on its power, economy and emissions [5], such as improving combustion performance, reducing pollutant emissions and increasing diesel engine power [6]. The ideal fuel injection system has the characteristics of high injection pressure, flexible adjustment of the injection law and injection timing [7].…”
Section: Introductionmentioning
confidence: 99%
“…This can be done using various techniques, but in this study, min-max normalization was applied. A detailed description of such a method utilized by the authors can be found in [23].…”
Section: A) B)mentioning
confidence: 99%